Association Between Minor Salivary Gland Biopsy During Sjӧgren’s Syndrome and Serologic Biomarkers: A Systematic Review and Meta-Analysis - Berardicurti, Onorina; Ruscitti, Piero; Di Benedetto, Paola; D’Andrea, Settimio; Navarini, Luca; Marino, Annalisa; Cipriani, Paola; Giacomelli, Roberto (Frontiers in Immunology, 2021)
Objective: Patients with primary Sjӧgren’s syndrome (pSS) may develop a potentially severe disease with extra-glandular involvement and lymphoma insurgence. Minor salivary gland biopsy is routinely used in the disease diagnosis, but its potential role as a biomarker for clinical disease presentation and prognosis is still poorly understood. Methods: We performed a systematic review and meta-analysis on clinical presentation and prognosis in pSS patients who underwent to minor salivary gland biopsy at diagnosis according to the PRISMA guidelines. Results: We included 5 retrospective studies and 589 pSS patients. Ectopic GC presence was not associated with a significant increase in the odds ratio for the clinical variables explored such as salivary gland swelling, arthritis and Raynaud’s phenomenon. As far as serological features are concerned, ectopic GC presence accounted for an increased ratio of antibodies anti-SSA (OR=3.13, 95% CI: 1.25-7.85, p=0.02, I2=79%), anti-SSB (OR=3.94, 95% CI: 1.50-10.37, p=0.0005, I2=80%), and RF presence (OR=3.12, 95% CI: 1.94-5.00, p<0.00001, I2=0%). Conclusions: This study showed that the association between ectopic GC in salivary glands identifying a clinical subset characterized by autoantibodies presence and probably affected from a more severe disease.